GROWING POTATO SPROUTS UNDER LIGHT EMITTING DIODES - Khalil, Mohammad Mustafa (Potato Journal, 2017)
Lighting emitting diodes (LEDs) offer a good tool for use in agricultural applications. Potato sprouts used for varieties distinctness, uniformity and stability (DUS) tests. The aim of this study is to test the validity of using LEDs for growing potato sprouts. 15 varieties were exposed to 5 light sources white LEDs, red LEDs, blue LEDs, red/blue LEDs and white florescent lamps. Â The obtained results indicated that white LEDs could be a good source of lighting for growing light sprouts for DUS tests. Red LEDs produced tall thin sprouts with the lowest dry weight. White fluorescent produced the highest anthocyanin content. Varietal differences observed between the 15 tested varieties in length, width, fresh weight, dry weight and anthocyanin content.